Is grip strength associated with length of stay in hospitalised older patients admitted for rehabilitation? Findings from the Southampton grip strength study. - Roberts, H; Syddall, H; Cooper, C; Aihie Sayer, A (2012)
BACKGROUND: identification of patients at risk of prolonged hospital stay allows staff to target interventions, provide informed prognosis and manage healthcare resources. Admission grip strength is associated with discharge outcomes in acute hospital settings. OBJECTIVE: to explore the relationship between grip strength and length of stay in older rehabilitation in-patients. DESIGN: single-centre prospective cohort study. SETTING: community hospital rehabilitation ward. SUBJECTS: one hundred and ten patients aged 70 years and over. METHODS: data on age, height, weight, body mass index (BMI), co-morbidities, medication, residence, grip strength, physical function, cognitive function, frailty, falls, discharge destination and length of stay were recorded. RESULTS: higher grip strength was associated with reduced length of stay, characterised by an increased likelihood of discharge to usual residence among male rehabilitation in-patients (hazard ratio 1.09 (95% confidence interval 1.01, 1.17) per kilo increase in grip strength, P = 0.02) after adjustment for age and size. CONCLUSIONS: this is the first prospective study to show that stronger grip strength, particularly among male in-patients, is associated with a shorter length of stay in a rehabilitation ward. This is important because it demonstrates that grip strength can be discriminatory among frailer people. Further research into the clinical applications of grip strength measurement in rehabilitation settings is needed.